Influence of caries risk on the retention of a resin-modified glass ionomer used as occlusal sealant: a clinical trial - Elaine Pereira da Silva TAGLIAFERRO; Vanessa PARDI; Gláucia Maria Bovi AMBROSANO; Marcelo de Castro MENEGHIM; Marco Aurelio Benini PASCHOAL; Rita de Cássia Loiola CORDEIRO; Antonio Carlos PEREIRA (Universidade Estadual Paulista, 2017)
Abstract Introduction Little is known whether caries risk influence occlusal sealants retention. Objective To determine the retention rates (RR) of the resin-modified glass ionomer cement used as occlusal sealant in permanent first molars of 6-8-year old schoolchildren and to analyze the influence of caries risk at baseline on the RR of the sealant, over a 24-month period. Material and method The sealant application was performed in a dental office at the beginning of the study, after children being allocated into high caries risk group (HR) and low caries risk group (LR). The examinations were performed by the same calibrated dentist at 0, 6, 12, 18 and 24 months. Retention rates were estimated, the Kaplan-Meier method was used to estimate the survival probabilities; and the comparison between HR and LR groups was evaluated by Wilcoxon and log-rank test. Result The results showed that 14% of sealed teeth showed total loss (16% for HR and 12% for LR) and 46% showed partial loss during the study (51% for HR and 41% for LR), in relation to the baseline sample. No difference could be demonstrated by the survival analysis between HR and LR groups (p>0.05). Conclusion Caries risk did not influence the retention rates of a resin-modified glass ionomer cement used as occlusal sealant in 6-8-year old schoolchildren.